Relationship of mild fatty liver, b-carotene, vitamins a and e status of periparturient holstein cows - Rosendo, Oswaldo; McDowell, Lee; Staples, Charles; Shearer, Jean; Wilkinson, Nancy; Seymour, William (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> The objectives of this study were to determine the association between mild fatty liver and b-carotene (BC), retinol (ROL), and a-tocopherol (AT) status. Multiparous Holstein cows were defined as having mild fatty liver using a threshold of 2% liver triacylglycerol (TAG, wet basis) at day (d) 2 after calving. Cows with mild fatty liver decreased dry matter intake (DMI) as a % of body weight (BW) from calving to 5th week (wk) of lactation (3.47 vs. 3.99, P = 0.02) and increased plasma nonesterified fatty acids (NEFA) concentration (345.0 vs. 266.0 Âµeq/dL, P = 0.10) as compared to normal cows. Fatty liver tended to lower plasma ROL (0.20 vs. 0.23 Âµg/mL, P = 0.10), but had no effect on plasma BC, plasma AT, liver BC, and liver ROL (P > 0.12) concentrations. However, depression in liver BC at calving was very small (8.0 vs. 68.0%) for fatty liver than for normal cows. Liver AT concentrations were greater (5.5 vs. 4.0 Âµg/g, P = 0.06) for cows with more than 2% liver TAG concentration. Concentration of plasma NEFA was positively correlated with plasma BC concentrations (r = 0.18, P < 0.05) and negatively correlated with concentrations of plasma ROL (r = -0.36, P < 0.0001) or AT (r = -0.35, P < 0.0001). A positive direct relationship between DMI and plasma vitamins status was found to exist only for ROL and AT, which suggests that stores of ROL or AT are less labile than stores for BC. At different times from calving, liver BC concentrations were positively correlated with liver TAG concentrations in a consistent manner but, correlations among liver ROL or liver AT concentrations and liver TAG concentrations were nonsignificants. The results suggest that the regulatory role of the liver in maintaining retinol concentrations in plasma may be compromise in cows with fatty liver.